Chapter 4 Levinas, hospitality and the feminine other - Lashley, Conrad (Taylor & Francis, 2017)
We could start this chapter by dishing up a vast array of interpretations and denitions, and refer to a number of debates in which the term hospitality takes centre stage. This would be done with the intention of illustrating the meaning and academic, societal or managerial relevance of hospitality. We will resist this temptation. We nd that a philosophical understanding of hospitality is often eclipsed by endeavours to ground its academic or societal relevance. Instead, this chapter aims to convey a particular understanding of hospitality according to the French philosopher Emmanuel Levinas (1906-1995). We read this philosophy as a philosophy of hospitality according to, but not based upon, the reading of his colleague, dear friend and fellow philosopher Jacques Derrida (see Derrida, 1999). The purpose is to shed light on the fundamental question of why and how people are hospitable towards others.